Investment expectations by vulnerable European firms: A difference-in-difference approach - Alexander Coad; Sofia Amaral-Garcia; Peter Bauer; Clemens Domnick; Péter Harasztosi; Rozália Pál; Mercedes Teruel (European Investment Bank (EIB), 2022)
The effect of the COVID shock on European economies has been severe and also unequal, with some firms being affected much more strongly than others. To improve the effectiveness of policy interventions, policymakers need to understand which types of vulnerable firms have been suddenly pushed into dire circumstances. We seek to fill this important gap in our knowledge by providing evidence from the EIBIS (European Investment Bank Investment Survey, 2016-2020) on how the COVID shock has affected the investment activity and investment-related framework conditions of vulnerable firms. While data on actual investment activity post-COVID is not yet available to us, we focus on investment expectations. We exploit the fact that the same questions relating to investment expectations have been asked in several previous survey waves, which enables a difference-indifferences approach to investigate how investment expectations might have suddenly changed, for vulnerable groups of firms, immediately after the onset of the COVID crisis. We focus on 4 groups of vulnerable firms: High-Growth Enterprises (HGEs), young and small firms, R&D investors and nonsubsidiary firms. R&D investors are more likely to be pessimistic about investment plans as a consequence of the COVID shock, and (similarly) HGEs are less likely to be optimistic about investment plans. R&D investors are less likely to be optimistic about the availability of internal finance, while HGEs and R&D investors are more likely to be pessimistic about the availability of external finance. Subsidiary firms, interestingly, are more likely to report a decrease in expected investment, although this could be part of a conservative group-level strategy and coordinated group-level reduction in investment, however that is not caused by any detectable lack of access to (internal or external) finance. Event study graphs generally confirm our regression results.
Keywords: 330